Public science, private science and S&T gender segregation in Europe - Oliveira, L.; Carvalho, H. (9th Conference of the European Sociological Association: European Societies or European Societies?, 2009)
This paper has two main goals. The first is to analyse how European countries differ, or not, in terms of a dominant pattern of public/private science. The second is to analyse if and how those patterns are related with gender discrimination in S&T. The implicit hypothesis is that dominant patterns of private and/or public science are related with the stratification of S&T European Space and that different types of gender discrimination existing in European Higher Education systems (Oliveira & Carvalho, 2008) can be extended to the private and public science sectors as well. In the pursuit of the first goal, methods of multidimensional analysis are applied in order to identify configurations of European countries based on indicators, namely the employment distribution of researchers across the four sectors (Government, business enterprise sector, private non profit sector and Higher Education) and S&T expenditure by country. Five patterns were identified that distinguish groups of countries from each other, revealing the existence of different situations among EU countries. One group consists of central and northern European countries. The eastern European countries belong to two different groups. One also includes Spain and Greece and another Portugal and Italy. Luxembourg and Bulgaria present two other different patterns, consequently defining each as a cluster. We therefore analysed gender discrimination in the four above mentioned sectors by country. Finally, we evaluated to what extent the previously identified five European private/public patterns are distinct from each other in relation to gender discrimination indicators.